On the use of a variable coefficient of reflectivity associated with an augmented area-to-mass ratio to de-orbit CubeSats - Silva Neto, J. B.; Prado, A. F.B.A.; Sanchez, D. M.; Formiga, J. K.S. [UNESP] (IOP Publishing, 2017)
The number of missions involving CubeSats increases each year, including Brazilian missions. The simplification of the projects, aiming smaller structures and less weight, makes the missions of CubeSats cheaper compared to large satellites. Another point is that, in recent years, the concern about the increase of objects in orbit becomes important, since operational satellites and upper stage of launchers that populate the Low Earth Orbit region (LEO region) are more numerous. To try to reduce the impact of this problem, there is a consensus that objects in LEO region should re-enter in the atmosphere within 25 years. This is becoming a limit for projects of CubeSats. In this scenario, the present paper presents an alternative to this problem, which is the use of devices of area augmentation and/or variation of the coefficient of reflectivity in a CubeSat. By using these devices, it is possible, even in regions where the air density is not sufficiently large or where there is no more atmosphere, to force the decay of a CubeSat. Then, one can carry out missions of CubeSat to aim for higher altitudes than current missions, expanding the possibilities of applications.